2003
DOI: 10.1161/01.cir.0000087595.17277.73
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced G i Signaling Selectively Negates β 2 -Adrenergic Receptor (AR)– but Not β 1 -AR–Mediated Positive Inotropic Effect in Myocytes From Failing Rat Hearts

Abstract: Background-Myocardial contractile response to ␤ 1 -and ␤ 2 -adrenergic receptor (AR) stimulation is severely impaired in chronic heart failure, in which G i signaling and the ratio of ␤ 2 /␤ 1 are often increased. Because ␤ 2 -AR but not ␤ 1 -AR couples to G s and G i with the G i coupling negating the G s -mediated contractile response, we determined whether the heart failure-associated augmentation of G i signaling contributes differentially to the defects of these ␤-AR subtypes and, if so, whether inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 52 publications
6
110
1
Order By: Relevance
“…Interestingly, epinephrine exhibits a ϳ200-fold greater potency for activating the G i pathway than activating the G s pathway at recombinant ␣ 2C(10) -adrenoceptors, whereas the imidazoline agonist oxymetazoline only stimulates the G i pathway (Eason et al, 1994). Furthermore, during submission of this work, an article supporting the concept of agonist-dependent selectivity for coupling of rat cardiac ␤ 2 -adrenoceptors was published (Xiao et al, 2003). These authors showed that the positive inotropic effects of the ␤ 2 -selective agonists salbutamol, zinterol, and procaterol, but not of fenoterol, are enhanced by PTX.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, epinephrine exhibits a ϳ200-fold greater potency for activating the G i pathway than activating the G s pathway at recombinant ␣ 2C(10) -adrenoceptors, whereas the imidazoline agonist oxymetazoline only stimulates the G i pathway (Eason et al, 1994). Furthermore, during submission of this work, an article supporting the concept of agonist-dependent selectivity for coupling of rat cardiac ␤ 2 -adrenoceptors was published (Xiao et al, 2003). These authors showed that the positive inotropic effects of the ␤ 2 -selective agonists salbutamol, zinterol, and procaterol, but not of fenoterol, are enhanced by PTX.…”
Section: Discussionmentioning
confidence: 89%
“…Also, the stimulation of 2ARs by isoproterenol causes an initial increase in contraction rate followed by a sustained decrease in murine cardiomyocytes (Devic et al, 2001;Wang et al, 2008), suggesting some cardioinhibitory role for the receptor. This is further supported by the observation that disruption of G i activity by pertussis toxin (PTX) enhances the 2AR-mediated contractile response of murine (for reviews, see Xiao, 2001;Xiao et al, 2003) and canine (Kuschel et al, 1999) cardiomyocytes. Indeed, while the 2AR-G i complex does not seem to directly inhibit global cAMP production, it does seem to affect downstream PKA activity and also the association of 2ARs with G s proteins.…”
Section: 2armentioning
confidence: 87%
“…Many factors including subcellular localization (e.g. caveolae) (Rybin et al, 2000), changes in conformation, dual coupling to G s and G i proteins, and agonist-mediated internalization of the receptor can all play a role in how 2AR affects different cell signalling pathways (for reviews, see Xiao et al, 2003;Zheng et al, 2004).…”
Section: 2armentioning
confidence: 99%
“…Thus, in isolated ventricular cardiomyocytes from spontaneously hypertensive rats (SHR) with heart failure, the contractile response to several β 2 AR-agonists, including terbutaline, salbutamol, zinterol, and procaterol, could be markedly enhanced when the cardiomyocytes were pretreated with pertussis toxin (PTX), thereby inactivating the G iprotein. Interestingly, however, the contractile response to another β 2 AR-agonist, fenoterol, was not affected by PTX-treatment (11). Similarly, in rat ventricular cardiomyocytes, fenoterol fully inhibited phenylephrineevoked hypertrophic response [evoked by α 1A AR stimulation (12)], while terbutaline and salbutamol evoked only partial inhibition.…”
Section: β-Adrenoceptorsmentioning
confidence: 92%